Instant Messaging for Creating Interactive and Collaborative m-Learning Environments - Kadirire, James (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2007)
'Instant Messaging' (IM) and 'Presence,' which is essentially the ability of being able to detect if other users are logged in on the network and send them messages in real time, has become one of the most popular applications of the Internet, causing people to want to stay connected to the Internet for inordinate amounts of time, a phenomena that also fosters a sense of "online community," that perhaps no other application has done previously (Alvestrand, 2002). This research looks at the use of mobile devices to send instant messages that can carry much more information than the short message service (SMS) messages, but would be free to use, notwithstanding the price of getting online. We present a prototype IM system that can be used as a viable means of communicating and learning in higher education establishments. There is some evidence to show that learning using mobile devices reduces the formality of the learning experience, and helps engage reluctant learners and raise their self-confidence. In order for the learning process to be successful in online distance learning, unlike in the traditional face-to-face learning, attention must be paid to developing the participants' sense of community within their particular group. Instant messaging – or IM – is a natural medium for online community building and asynchronous/ synchronous peer discussions.